2020
DOI: 10.4025/actasciagron.v42i1.43469
|View full text |Cite
|
Sign up to set email alerts
|

Quality of rubber tree rootstock seedlings grown in protected environments and alternative substrates

Abstract: This study aimed to evaluate the quality of Hevea brasiliensis seedlings, a GT1 clone, produced in protected environments in a variety of substrates. The treatments consisted of 13 substrates composed of combinations of cattle manure, soil from a ravine, medium vermiculite, superfine vermiculite and washed fine sand and two environments: a greenhouse with 50% shade using aluminized screen and a plant nursery with 50% shade using a Sombrite® screen. There were no replications of the environments; therefore, eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…This corroborates the results of Pereira et al (2019) also in rubber tree seedlings of the GT1 clone, with apical pruning treatments. In testing substrates for GT1, PR255, and RRIM600 clones, Vieira et al (2016) obtained the same proportion, whereas Silva et al (2020) reported 34% in roots and 66% in shoot. Our findings show that the use of reflective material provides robust root systems, improving quality of seedlings and their settling in the field.…”
Section: Environmentmentioning
confidence: 81%
See 1 more Smart Citation
“…This corroborates the results of Pereira et al (2019) also in rubber tree seedlings of the GT1 clone, with apical pruning treatments. In testing substrates for GT1, PR255, and RRIM600 clones, Vieira et al (2016) obtained the same proportion, whereas Silva et al (2020) reported 34% in roots and 66% in shoot. Our findings show that the use of reflective material provides robust root systems, improving quality of seedlings and their settling in the field.…”
Section: Environmentmentioning
confidence: 81%
“…Some studies have shown production of better rubber tree rootstocks clone G1 by using 50% shading screen (Sombrite® and Aluminet®) when compared to direct sunlight (Vieira et al, 2016). In turn, when covered with low-density polyethylene, agricultural greenhouses have shown better results than the former mentioned screens (Silva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Esse foi obtido com a aplicação foliar de bioestimulante. Valores adequados de RMS devem variar de 1 a 2, ou seja, uma distribuição equilibrada (1/1) até no máximo o dobro (Carneiro, 1995;Silva et al, 2020). Mudas com RMS acima dos valores ideais indicam que a parte aérea é bem mais desenvolvida do que o sistema radicular.…”
Section: Resultsunclassified
“…Arg.] is a forest plant that produces natural rubber with properties suitable for the manufacturing sector (Silva et al, 2020). With significant development potential, primarily in tropical parts of the world (Yang et al, 2019), the harvested area increased by 3.3 million hectares between 2010 and 2020, particularly in Southwest Asia and China (Warren-Thomas et al, 2023).…”
Section: Introductionmentioning
confidence: 99%